Mutant BRAF V600E protein in ganglioglioma is predominantly expressed by neuronal tumor cells - Kölsche, Christian; Wöhrer, Adelheid; Jeibmann, Astrid; Schittenhelm, Jens; Schindler, Genevieve; Preusser, Matthias; Lasitschka, Felix; Deimling, Andreas von; Capper, David (Acta neuropathologica, 2013)
Ganglioglioma is a rare CNS tumor with a benign biological behavior. Recently, the BRAF V600E mutation was identified in approximately 20 % of gangliogliomas. Here, we analyzed a total of 71 gangliogliomas for BRAF V600E mutational status by VE1 immunohistochemistry and direct DNA sequencing. The BRAF V600E mutation was detected in 41/71 (58 %) gangliogliomas by immunohistochemistry. DNA sequencing was concordant in 60 of 62 analyzed cases. BRAF status was compared with clinical, histological and immunohistochemical data. Presence of the BRAF V600E mutation was associated with expression of synaptophysin in the tumor (p = 0.0008), presence of dysplastic neurons (p = 0.011) and lymphocytic cuffs (p = 0.018), and with younger age (p = 0.0054). Extensive hemosiderin deposition within the tumor was significantly associated with BRAF wild-type status (p = 0.042). No significant association was found with proliferation (p = 0.053), presence of phospho ERK (p = 0.1) or senescence marker p16INK4a (p = 0.22). Using VE1, we localized the BRAF V600E-mutated protein predominantly to the neuronal compartment, indicating that BRAF mutations occur in cells that have the capacity to differentiate into ganglionic cells. In many cases mutant BRAF is additionally expressed by the glial compartment, indicating that in these cases the cell targeted by BRAF mutation was likely capable of differentiating along both the ganglionic and glial lineages. No cases with an exclusive expression of BRAF V600E in the glial compartment were observed. Thus, using VE1 we identified the neuronal compartment as an essential part of this mixed glioneuronal tumor.